2018
DOI: 10.1038/bjc.2017.407
|View full text |Cite
|
Sign up to set email alerts
|

Reporting guidelines for oncology research: helping to maximise the impact of your research

Abstract: Many reports of health research omit important information needed to assess their methodological robustness and clinical relevance. Without clear and complete reporting, it is not possible to identify flaws or biases, reproduce successful interventions, or use the findings in systematic reviews or meta-analyses. The EQUATOR Network (http://www.equator-network.org/) promotes responsible reporting and the use of reporting guidelines to improve the accuracy, completeness, and transparency of health research. EQUA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…While the novice did receive training and benefited from a pilot period, others who have used the CERT have reported no difficulties in using the Explanation and Elaboration Statement and Checklist. 54,55 Completeness of reporting has been investigated for the CONSORT Statement [56][57][58][59][60] and the TIDieR Checklist. 7,56 Inter-rater reliability has not been routinely evaluated for reporting guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the novice did receive training and benefited from a pilot period, others who have used the CERT have reported no difficulties in using the Explanation and Elaboration Statement and Checklist. 54,55 Completeness of reporting has been investigated for the CONSORT Statement [56][57][58][59][60] and the TIDieR Checklist. 7,56 Inter-rater reliability has not been routinely evaluated for reporting guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Completeness of reporting has been investigated for the CONSORT Statement [56][57][58][59][60] and the TIDieR Checklist. 7,56 Inter-rater reliability has not been routinely evaluated for reporting guidelines. We located one example for the TIDieR Checklist 61 in which the authors reported that the PABAK coefficient was 'substantial' or 'almost perfect' (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting such large-scale use could allow for improved data mapping in clinical registries, improving data quality and interoperability 30. As previously exhibited in oncology research, broad adoption of a reporting standard can maximise the value and impact of research studies as well as the associated research data 31. This is because research redundancy is reduced, and interpretable research outputs and comprehensive datasets are produced 31.…”
Section: Discussionmentioning
confidence: 99%
“…As previously exhibited in oncology research, broad adoption of a reporting standard can maximise the value and impact of research studies as well as the associated research data 31. This is because research redundancy is reduced, and interpretable research outputs and comprehensive datasets are produced 31. A given standard may be more widely adopted if advocated by databases, funding bodies and scientific journals, geared towards kidney disease research, specifically.…”
Section: Discussionmentioning
confidence: 99%
“…As previously exhibited in oncology research, widespread utilization of the developed reporting guideline can function to reduce data and reporting inconsistency and redundancy across systems, as well as promote collaboration and(or) interoperability between systems (Biology et al, 2000;Hartwell et al, 2012;MacCarthy et al, 2018). Promoting such broad use could allow for improved data mapping in clinical registries, improving data quality and interoperability (Rastegar-Mojarad et al, 2017).…”
Section: Data Analysis Ementioning
confidence: 99%